O papel do cinema na construção da geografia anticolonial - Alves, Ludmila Pereira (2023)
This dissertation aims to establish a relationship between two ways of producing knowledge: Geography and Cinema, one in science and the other in art. Both are largely visual and endowed with a notorious power of synthesis. Cinema, as Nascimento (2018) suggests, is perhaps the greatest manifestation of imperative visual culture in modernity. More than establishing an interdisciplinary dialogue between geography and cinema, this research intends to establish a critique, departing from cinema to a conventional way of conceiving Geography.